Nonverbal Communication and its Effects on Human Relations: An Analysis from Surah Luqman - Yusuf, Tajudeen (QiST: Journal of Quran and Tafseer Studies, 2025)
Communication is a fundamental aspect of human relations and interactions, encompassing both verbal and nonverbal elements. While much emphasis is placed on verbal communication, nonverbal cues such as body language, facial expressions, and gestures often carry significant weight in conveying messages. The study of nonverbal communication has garnered attention across various disciplines, including psychology, sociology, and anthropology. However, the exploration of nonverbal communication through the lens of religious texts, particularly the Qur'an, remains relatively underexplored. This paper seeks to fill this gap by examining the teachings of Surah Luqman, a chapter in the Qur'an that offers profound wisdom on ethical conduct and human relationships. By integrating Islamic exegesis with psychological theories and contemporary research on nonverbal communication, this study aims to provide a holistic understanding of the role of body language and other nonverbal cues in fostering positive human relations.The analysis will focus on how nonverbal communication, as implied in the verses, influences human relations and the ethical principles that govern such interactions. The results of the study show that, in contemporary times, the relevance of these principles remains strong, as they provide a framework for addressing modern communication challenges. By adhering to the Islamic guidelines of honesty, respect, and empathy in communication, individuals can cultivate positive interpersonal relations that contribute to personal and communal well-being.